Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Saintifik pada Mata Pelajaran Teknologi Perkantoran Kelas X OTKP di SMK Ketintang Surabaya - Abdul Aziz Al-Rizal; Novi Trisnawati (Universitas Negeri Surabaya, 2020)
Development of Student Activity Sheet (LKPD) Based on Scientific Approach aims to describe or define the process of developing a scientific-based LKPD and plan or design of a scientific-based LKPD developed, this development research uses the type of research development Research and Development (R&D). This study uses a 4-D development model from Thiagarajan which has four stages consisting of the defining stage, the design stage, the develop phase, and the disseminate stage. However, this research did not carry out the development stage and the dissemination stage because the research carried out only focused on defining and designing the developed LKPD. Observation results indicate that the teaching materials used are still somewhat inadequate, because the teaching materials used are only from publishers only and are not in accordance with the Office Technology syllabus. Thus, innovative, creative, and appropriate teaching materials are needed in accordance with the applicable syllabus and curriculum. The developed LKPD uses a scientific approach that is in accordance with the 2013 revised 2017 curriculum which contains 5 M tasks (observing, asking questions, gathering information, reasoning, communicating). The results of this study describe how the process of defining a scientific-based LKPD was developed and describe the planning or design process of a scientific-based LKPD that was developed along with a literature review that supports it.